Tata Kelola (Collaborative Governance) dalam Pengelolaan Sampah Organik di Pusat Daur Ulang Jambangan Kota Surabaya - Megananda, Astrid; M. Kendry Widiyanto; Dida Rahmadanik (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze collaborative governance in organic waste management at the Recycling Center (PDU) Jambangan, Surabaya City. The research employs a descriptive qualitative method by collecting data through in-depth interviews, direct observations in the field, and relevant documentation. The findings indicate that the collaboration process between the government, the community, and Regional Owned Enterprises (BUMD), specifically PDAM Kota Surabaya in their role as Corporate Social Responsibility (CSR) executors, has been effectively implemented despite facing several challenges. Using the collaborative governance framework proposed by Ansell and Gash, this study finds that the success of collaboration heavily relies on facilitative leadership that can build trust and commitment among stakeholders. This collaborative process includes regular face-to-face dialogues, trust-building through transparency and openness, strong commitment to the process, continuous enhancement of shared understanding, and interim results achieved as motivation to continue the cooperation. This study concludes that collaborative governance at PDU Jambangan has made a significant contribution in reducing the volume of organic waste and enhancing public awareness of the importance of effective waste management. This success is achieved through joint efforts between the government, the community, and PDAM Kota Surabaya in creating a sustainable and environmentally friendly waste management system